2022
DOI: 10.1007/s00439-021-02427-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of novel NAA10 variants suggests distinct pathogenic mechanisms involving impaired protein N-terminal acetylation

Abstract: NAA10 is the catalytic subunit of the N-terminal acetyltransferase complex, NatA, which is responsible for N-terminal acetylation of nearly half the human proteome. Since 2011, at least 21 different NAA10 missense variants have been reported as pathogenic in humans. The clinical features associated with this X-linked condition vary, but commonly described features include developmental delay, intellectual disability, cardiac anomalies, brain abnormalities, facial dysmorphism and/or visual impairment. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In regard to the biochemical analyses published to date, most variants have been primarily studied using either immunopurified overexpressed full-length NAA10 (235 residues) protein from yeast (Van Damme et al 2014) or mammalian culture (Myklebust et al 2015; McTiernan et al 2021, 2022; Støve et al 2018; Bader et al 2020), S. frugiperda ( Sf 9)-expressed recombinant NatA complex containing a C-terminally truncated NAA10 (1-160) (Cheng et al 2019), or an affinity-tagged full-length NAA10 expressed in E. coli (Rope et al 2011; Popp et al 2015; Saunier et al 2016; Myklebust et al 2015; McTiernan et al 2018; Rasmus Ree et al 2019; Casey et al 2015). Each of these methodologies have their limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In regard to the biochemical analyses published to date, most variants have been primarily studied using either immunopurified overexpressed full-length NAA10 (235 residues) protein from yeast (Van Damme et al 2014) or mammalian culture (Myklebust et al 2015; McTiernan et al 2021, 2022; Støve et al 2018; Bader et al 2020), S. frugiperda ( Sf 9)-expressed recombinant NatA complex containing a C-terminally truncated NAA10 (1-160) (Cheng et al 2019), or an affinity-tagged full-length NAA10 expressed in E. coli (Rope et al 2011; Popp et al 2015; Saunier et al 2016; Myklebust et al 2015; McTiernan et al 2018; Rasmus Ree et al 2019; Casey et al 2015). Each of these methodologies have their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The structures were visually inspected using PyMol, which was also used in conjunction with Adobe Illustrator CC to prepare Figure 4 and Figure 5. The discussion was also informed by numerous biochemical and biophysical studies of NAA10 and NAA15 mutant proteins 13,16,[18][19][20][21]23,32,33 .…”
Section: Molecular Analysis Of Naa10 and Naa15 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike lysine acetylation, the most exhaustively studied acetylation type, Nt-acetylation has been regarded as an irreversible and static modification, as no deacetylase acting on N-termini has yet been identified ( 2, 4 ). Nevertheless, different reports suggested that Nt-acetylation may be regulated by cellular signaling and its cellular status can vary in different disease states and biological processes such as cancer( 10 ), developmental disorders( 11, 12 ), drought stress( 7, 13 ), calorie restriction and Ac-CoA availability( 14, 15 ) or apoptotic fate( 16, 17 ). Thus, Nt-acetylation has emerged as an important protein modification that is involved in the regulation of different biological pathways.…”
Section: Introductionmentioning
confidence: 99%